2017
DOI: 10.1039/c7ra05044e
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin-enhanced biosynthesis of antimicrobial AgNPs by improving the phytochemical reducing potential of a callus culture of Ocimum basilicum L. var. thyrsiflora

Abstract: We describe the synthesis of AgNPs using Ocimum basilicum L. var. thyrsiflora leaf derived callus extracts formed in response to thidiazuron alone and a combination of TDZ melatonin which act both as reducing and stabilizing agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 66 publications
(64 reference statements)
1
3
0
1
Order By: Relevance
“…The results are in agreement with Riaz and coauthors [74] who observed that Melatonin significantly increased TPC values. Similar results were also found by Sumaira and coauthors [75] and Sheshadri and coauthors [76] also reported that Melatonin greatly enhances the biosynthesis of phytochemicals.…”
Section: Total Phenolic Contentsupporting
confidence: 87%
“…The results are in agreement with Riaz and coauthors [74] who observed that Melatonin significantly increased TPC values. Similar results were also found by Sumaira and coauthors [75] and Sheshadri and coauthors [76] also reported that Melatonin greatly enhances the biosynthesis of phytochemicals.…”
Section: Total Phenolic Contentsupporting
confidence: 87%
“…The pasteurization causes Maillard reactions which create more anti-oxidant chemicals and possibly consume less melatonin [ 51 ]. Most importantly, a powerful anti-microorganism activity of melatonin was uncovered during juice storage, although melatonin is a molecule frequently reported to reduce the biotic stress and inhibit the growth of microorganisms in plants [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ], this effect on food storage was not known, especially in the fresh juice with a shelf life of less than 4 hours. Our results showed that melatonin significantly inhibited the total microorganisms, including bacteria, moulds and yeasts during the juice storage during the tested time from 4 to 12 h ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Their versatile implementation spans a multitude of manufacturing processes, encompassing the realms of rubbers, plastics, ceramics, glass, cement, lubricants, paints, ointments, adhesives, sealants, pigments, foods, flame retardants, and even first-aid tapes [17,18]. The advent of the green synthesis method through the employment of plant extracts has captured considerable attention as a viable and simplistic alternative to conventional physical and chemical approaches [19][20][21][22][23][24]. This ecofriendly methodology boasts inherent advantages such as facile handling and the abundant availability of plant resources, positioning it as a highly desirable avenue for scientific exploration [25].…”
Section: Introductionmentioning
confidence: 99%